Musical Psychology - Julmatova Saodat Juratjon Qizi (Research Parks Publishing LLC, 2021)
Psychology of Musical Perception. Listening to music should be considered as a basic activity in the art of music, just like writing and playing music. And without a listener, the art of music loses its meaning and ceases to exist. Listening to and perceiving music is a type of musical activity that is nurtured and absorbed from childhood. It is said that everyone hears music, but not everyone listens to it. The level of comprehension in the process of listening to music depends on the general culture of the listener and the level of musical preparation, and is directly proportional to it. A complete and deep understanding of a piece of music is also a testament to the skill of the composer and performer. In this way, it can be concluded that the listening process is an integral part of the listener’s upbringing, individual abilities and preparation.